Critical care nurses' experiences of caring challenges during post-resuscitation period: a qualitative content analysis - Mahnaz Zali; Azad Rahmani; Hadi Hassankhani; Hossein Namdar-Areshtanab; Neda Gilani; Arman Azadi; Mansour Ghafourifard (BMC, 2024)
Abstract Background Patients in the post-resuscitation period experience critical conditions and require high-quality care. Identifying the challenges that critical care nurses encounter when caring for resuscitated patients is essential for improving the quality of their care. Aim This study aimed to identify the challenges encountered by critical care nurses in providing care during the post-resuscitation period. Methods A qualitative study was conducted using semi-structured interviews. Sixteen nurses working in the intensive care units of three teaching hospitals were selected through purposive sampling. The Data collected were analyzed using qualitative content analysis. Results Participants experienced individual, interpersonal, and organizational challenges when providing post-resuscitation care. The most significant challenges include inadequate clinical knowledge and experience, poor management and communication skills, lack of support from nurse managers, role ambiguity, risk of violence, and inappropriate attitudes of physicians towards nurses' roles. Additionally, nurses expressed a negative attitude towards resuscitated patients. Conclusion Critical care nurses face several challenges in providing care for resuscitated patients. To enhance the quality of post-resuscitation care, address the challenges effectively and improve long-time survival it is crucial to implement interventions such as In-service education, post-resuscitation briefing, promotion of interprofessional collaboration among healthcare teams, providing sufficient human resources, clarifying nurses' roles in the post-resuscitation period and increasing support from nursing managers.